A infecção por Trypanosoma cruzi e a forma recombinante da sua proteína P21 altera a migração de células de câncer de mama triplo-negativo e de células não tumorais - Silveira, Anna Clara Azevedo (2021)
Several studies have shown that extracts, proteins and Trypanosoma cruzi itself have an action in reducing tumors in animal models and in cell cultures. The recombinant protein P21 from T. cruzi performs different biological activities such as chemotactic activity for immune system cells, inhibits angiogenesis and negatively modulates the replication of the parasite. Furthermore, it was observed that this protein binds to the CXCR4 chemokine receptor. Thus, this study aimed to evaluate the impact of rP21 and T. cruzi infection on triple-negative breast cancer cells and non-tumor epithelial cells. Initially, we performed the viability test and it was seen that the treatment with rP21 and the infection by T. cruzi up to 72 hours, did not present a viability lower than 50%. After the viability test, we verified the rate of invasion, multiplication and hatching of the parasite in the supernatant. The normal breast cell line, MCF-10A, is susceptible to infection by T. cruzi, being able to provide a favorable environment for the replication and differentiation of the parasite and the release of viable infective forms. The triple-negative MDA-MB-231 breast cell is also susceptible to parasite infection. After treatment with rP21 and T. cruzi infection, a decrease in migration of both treated groups was noted. After treatment with rP21 and infection by T. cruzi, a decrease in migration of both treated groups was noted. Furthermore, we observed that the rP21 protein after 3 hours labeling is located in the cell nucleus, which may be related to the CXCR4 receptor. Our results show that the expression of CXCR4 in the MDA-MB-231 cell decreases over time, but it presents a growth curve and a decrease in fluorescence at the observed times, suggesting a translocation of the CXCR4 receptor over time. In MCF-10A cells, fluorescence over time did not show any significant difference. When we observed the interaction of T. cruzi infection with the CXCR4 receptor, we saw that there is an interaction between them in MDA-MB-231 and MCF-10A cells, suggesting a relationship between migration/invasion and proliferation of these cells. In conclusion, rP21 and other T. cruzi molecules may be potential targets for the discovery anti-tumor drugs.